Brain tumors and COVID-19: the patient and caregiver experience*. Issue 1 (23rd August 2020) - Voisin, Mathew R; Oliver, Kathy; Farrimond, Stuart; Chee, Tess; Arzbaecher, Jean; Kruchko, Carol; Maher, Mary Ellen; Tse, Chris; Cashman, Rosemary; Daniels, Maureen; Mungoshi, Christine; Lamb, Sharon; et al.
Abstract: Background: Since the COVID-19 pandemic began, thousands of medical procedures and appointments have been canceled or delayed. The long-term effects of these drastic measures on brain tumor patients and caregivers are unknown. The purpose of this study is to better understand how COVID-19 has affected this vulnerable population on a global scale. Methods: An online 79-question survey was developed by the International Brain Tumour Alliance, in conjunction with the SNO COVID-19 Task Force. The survey was sent to more than 120 brain tumor charities and not-for-profits worldwide and disseminated to pediatric and adult brain tumor patients and caregivers. Responses were collected from April to May 2020 and subdivided by patient versus caregiver and by geographical region. Results: In total, 1989 participants completed the survey from 33 countries, including 1459 patients and 530 caregivers. There were no significant differences in COVID-19 testing rates ( P = .662) or positive cases for brain tumor patients between regions ( P = .1068). Caregivers were significantly more anxious than patients ( P ≤ .0001). Patients from the Americas were most likely to have lost their jobs due to the pandemic, practiced self-isolation, and received telehealth services ( P ≤ .0001). Patients from Europe experienced the most treatment delays ( P = .0031). Healthcare providers, brain tumor charities, and not-for-profits were ranked as the most trusted sources of information. Conclusions: As a result of COVID-19, brain tumor patients and caregivers have experienced significant stress and anxiety. We must continue to provide accessible high-quality care, information, and support in the age of COVID-19.